Best Answer

square root of 4x is 2 Times Square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

Q: Square root of 4x plus the square root of x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

4x to the sixth can be expanded to (4x * 4x * 4x)(4x * 4x * 4x) or (4x to the third)(4x to the third) the square root of the above would be 4x to the third

x2 + 4x = 41

x^2 + 4x + 2 = 0 doesn't factor neatly. Using the quadratic formula, we find two solutions: -2 plus or minus the square root of 2 x = -0.5857864376269049 x = -3.414213562373095

sqrt(10x)*sqrt(8x) = sqrt(80x2) = sqrt(16x2*5) = sqrt(16x2)*sqrt(5) = 4x*sqrt(5)

X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2

Related questions

The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.

We use the property of square roots that says the square root of (ab)=square root (a) multiplied by square root of b So square root (4x)=square root (4) mutiplies by square root of x =2(square root (x)) 2sqrt(x)

No.

4x-8x = -4x √-4x stands. However, x could not possibly be a positive number, because: (Negative) X (Positive) = (Negative) The square root of a negative number is undefined-so... (√-4x) + 9 Is your answer.

4x to the sixth can be expanded to (4x * 4x * 4x)(4x * 4x * 4x) or (4x to the third)(4x to the third) the square root of the above would be 4x to the third

If you square an expression and then take the square root, the squaring and the square root cancel one another, EXCEPT that the sign will be positive. Thus, if you square 16x, and then take the square root, the answer can be 16x or -16x, depending on whether "x" is positive or negative. Or if you only square x, and then take the square root of the entire expression, it would be 4x or -4x (once again, depending on whether "x" is positive or negative).

y=(8x).5 + (4x).5 = (2+2sqrt(2))x.5 y'=(1 + sqrt(2))/sqrt(x)

x2 + 4x = 41

If you mean: 4*square root of x2 then it is 4x

No. The square root of 16 is.... 4 (4x4=16) and (-4x-4=16)

Using the quadratic equation formula the values of x are: x = -2 - the square root of 5 and also x = -2 + the square root of 5

The square root of the left hand side is 2*(x - 1).The square root of the right hand side is 2*sqrt(14)